Pareto optimal approach in Multi-Objective Chaotic Mutation Immune Evolutionary Programming (MOCMIEP) for optimal Distributed Generation Photovoltaic (DGPV) integration in power system - Syed Mustaffa S.A.; Musirin I.; Mohamad Zamani M.K.; Othman M.M. (Ain Shams University, 2023)
Computer programming; Distributed power generation; Evolutionary algorithms; Integration; Pareto principle; Renewable energy resources; Voltage control; Fast voltage stability indices; Multi objective; Optimal; Pareto-optimal; Photovoltaic; Distributed computer systems